2006
DOI: 10.1016/j.joca.2005.12.012
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and ultrasonographic findings related to knee pain in osteoarthritis

Abstract: Suprapatellar effusion, Baker's cyst, and higher BMI are more frequent and seem to be risk factors of painful flare in OA of the knee.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(58 citation statements)
references
References 24 publications
4
53
1
Order By: Relevance
“…In OA, sonography has shown its capability in detecting and evaluating a large number of abnormalities involving hyaline cartilage, synovial fluid and synovial membrane, menisci, joint capsule and bursae as well as in the bony cortex [1,11,21,[23][24][25][26][27][28][29][30][31][32][33][34][35][36]. Recent development of high-resolution transducers and more powerful machines has rendered US an emerging and even more widely used tool to image and investigate both early and late changes in OA [9,11,17,32,33].…”
Section: Why To Use Sonography In Oa?mentioning
confidence: 99%
“…In OA, sonography has shown its capability in detecting and evaluating a large number of abnormalities involving hyaline cartilage, synovial fluid and synovial membrane, menisci, joint capsule and bursae as well as in the bony cortex [1,11,21,[23][24][25][26][27][28][29][30][31][32][33][34][35][36]. Recent development of high-resolution transducers and more powerful machines has rendered US an emerging and even more widely used tool to image and investigate both early and late changes in OA [9,11,17,32,33].…”
Section: Why To Use Sonography In Oa?mentioning
confidence: 99%
“…High BMI scores of healthy people have been shown to be a significant risk factor for the development of radiographic knee OA in later life32 ) . This is due to the mechanical loading, particularly on the lower extremities, of obesity33 ) . It has also been reported that the various adipokines expressed in adipose tissue, such as leptin, adiponectin, resistin, and visfatin, have shown a catabolic effect on articular cartilage34, 35 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Conflicting results have been reported regarding the relationship between the radiological grade of knee OA, pain, and function loss. Reasons have been suggested for this, such as radiographs being taken at different times, interpretation by different researchers, and the use of different methods for grading31, 33 ) . In the current study, a significant positive correlation was determined between the grade of knee OA and the pain and functional evaluation scores.…”
Section: Discussionmentioning
confidence: 99%
“…The ratio of painful osteoarthritic knee effusion ranges from 44% to 79% 2,3 . However, 16% of osteoarthritic knee effusion is painless 4 .…”
Section: To the Editormentioning
confidence: 99%